Effect of dangke administration on serum TNF-a and liver SOD levels in rats induced by a high-fat, high-sugar diet - Uzifatun Nur Y.F Lapatta; Diana Nur Afifah; Ardiyan Pramono; Ninik Rustanti (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Dangkes contain lactic acid bacteria that improve obesity by controlling the intestinal flora, improving the micro-ecological balance in the gut, and boosting the immune system. This study aimed to analyze the differences in serum TNF-α and liver SOD levels in obese rats fed a Dangke diet. The research was conducted from December to January 2024 at the PSPG PAU UGM using a true-experiment design post-test with only the control group. Male Sprague-Dawley rats (n=30) were randomly divided into five groups: healthy rats (KS), obese rats given standard feeding (K-), obese rats received L-Bio (K+), obese rats were given Dangke at a low dose (P1), and obese rats received Dangke at a high dose (P2). Intervention for 28 days. Data analysis was performed using one-way ANOVA tests and further post-hoc Bonferroni tests. The result obtainded that Dangke with dose dose of 3,6 g/200 gBB was effective in decreasing TNF-α levels and increasing SOD levels (p<0,05). P2 had the lowest mean TNF-α level (7,33 ± 0,22) compared to K+ (8,59 ± 0,22) and P1 (8,88 ± 0,18). P2 had the highest SOD levels compared to K+ (62,56 ± 4,06) and P1 (61,47 ± 4,71). In conclusion, Dangke effectively overcame inflammation and oxidative stress in obesity.